2020
DOI: 10.1007/s10965-020-02227-w
|View full text |Cite
|
Sign up to set email alerts
|

Effective removal of dyes from aqueous solutions using a novel antibacterial polymeric adsorbent

Abstract: Here, ethylenediamine-epichlorohydrin-trichlorophenol (EET) cross-linked polymer was synthesized and characterized by Fourier Transforms Infrared spectroscopy (FTIR), thermogravimetric analysis (TGA-DSC) and scanning electron microscopy (SEM). EET exhibited substantial antibacterial activity with inhibition zones of 38 and 64 mm against E. coli and S. aureus bacteria. Therefore, it was applied to treat methyl orange (MO) and rhodamine B (RB) dyes containing synthetic aqueous solutions under varying operation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Table 2 compares the performance of Li/ZNF with various materials in terms of TCP degradation. To degrade TCP, high amounts of catalysts (500–1000 mg.L‐1) were utilized in these studies, and the authors reported high efficiency of 95 to 100 %, which was achieved in 45 to 100 min [51–54] . Although various operational settings were used in each of these investigations, the performance of the Li/ZNF is comparable even at a low dose.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 compares the performance of Li/ZNF with various materials in terms of TCP degradation. To degrade TCP, high amounts of catalysts (500–1000 mg.L‐1) were utilized in these studies, and the authors reported high efficiency of 95 to 100 %, which was achieved in 45 to 100 min [51–54] . Although various operational settings were used in each of these investigations, the performance of the Li/ZNF is comparable even at a low dose.…”
Section: Resultsmentioning
confidence: 99%
“…To degrade TCP, high amounts of catalysts (500-1000 mg.L-1) were utilized in these studies, and the authors reported high efficiency of 95 to 100 %, which was achieved in 45 to 100 min. [51][52][53][54] Although various operational settings were used in each of these investigations, the performance of the Li/ZNF is comparable even at a low dose. Also, unlike the other catalysts, Li/ZNF can be easily retrieved from the reaction tank due to its magnetic properties.…”
Section: Plausible Photodegradation Mechanismmentioning
confidence: 99%
“…Wastewater contaminated with dyes is considered one of the most significant pollutants from the various industrial sources that cause severe environmental pollution. Many manufacturers of plastics, rubber, textiles, leather, paper, cosmetics, and food use dyes in their products, and the disposal of even small amounts of such can affect the ecosystem and result in serious environmental problems [2,3]. Therefore, removing dyes from wastewater is an important route to significantly reducing water and soil pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural wastes are mostly containing hemicellulose, lignin, and cellulose of high molecular weight. Some small-sized lignocellulosic materials are much important for the removal of dye molecules [ 20 , 21 , 22 ]. The agricultural wastes have been successfully applied for basic excluding of dyes as well as acid dyes.…”
Section: Introductionmentioning
confidence: 99%